A comparative study of chromosome G-banding using trypsin, papain, and pretreatment with emulphogene. Issue 5 (May 1979) - Khalid, G; Neumann, H; Flemans, R J; Hayhoe, F G
Abstract : G-banding of chromosome metaphase preparations derived from haemic cells of healthy individuals and from patients with acute myeloid leukaemia was performed with the aid of trypsin, papain, and pretreatment of the chromosome spreads with emulphogene before proteolytic digestion. Papain digestion revealed more distinguishable bands than did trypsin digestion. Pretreatment of the chromosome spreads with emulphogene greatly enhanced the number of distinguishable bands for both enzymes. The combination of pretreatment with emulphogene and digestion with papain revealed optimal numbers of bands for individual chromosomes essentially identical with those agreed at the Paris Conference 1971. The use of the emulphogene-papain technique appears also to offer an advantage in the banding of chromosomes from leukaemic cells.